Rock art as a source of contemporary cultural identity: a Siberian-Canadian Comparative Study - Rozwadowski, Andrzej (Faculty of Archaeology, Adam Mickiewicz University in Poznań, 2021)
This brief article is an introduction to a research project that examines the contemporary re- ception and re-interpretation/re-vitalization of prehistoric rock art and, more specifically, the re/ use of rock art motifs by present-day artists in Siberia and Canada. During the second half of the 20 th century, new artistic trends emerged in both regions, wherein artists significantly drew upon the heritage of indigenous peoples. In Canada, this phenomenon is mainly connected to works created by First Nations artists, while in Siberia it concerns a broader spectrum of image makers from indigenous and non-indigenous backgrounds. As a result, how the past is drawn upon in these two geographical regions involves differing perspectives, though some common trends can be observed. How do the artists link the past with the present through rock art, and to what extent do the images provide them with a source of identity? These are the questions examined by the project.
Keywords: rock art; identity, contemporary art; Siberia; Canada